Conceptualizing and measuring free and fair elections - Marta Regalia; Stefano Rombi (QOE-IJES, 2023)
The quality of elections is a rapidly growing field of study. There are numerous research methods and analysis techniques to examine it. However, literature still needs to shed full light on one of the main concepts associated with this area of research. Often, scholars refer to the concept of “free and fair elections” without providing a precise definition and identifying the dimensions connected to it. This article aims to help fill this gap by proposing a theoretical and operational definition of free and fair elections. For this purpose, the ten dimensions that make up the concept and the procedures to be followed to arrive at their measurement are described in depth. At the end of the analysis, we propose an index that measures the level of freedom and fairness of the elections.